2017
DOI: 10.22161/ijeab/2.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant growth promoting rhizobacterial (PGPR) inoculation on growth in tomato (Solanum Lycopersicum L.) and characterization for direct PGP abilities in Morocco

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 12 publications
1
5
0
1
Order By: Relevance
“…Such results were recently recorded in the work conducted by [48] with the inoculation of Serratia sp. on maize seeds grown on soil infested with Fusarium oxysporum and fertilized with N 180 P 140 K 90 and then in Morocco with the inoculation of Serratia proteamaculans (2025-1) on tomato [49]. Duponnois et al [50] indicated that the more robust the inoculated seedlings are than the un-inoculated plants, the more likely they are to survive by demonstrating a high capacity to withstand environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Such results were recently recorded in the work conducted by [48] with the inoculation of Serratia sp. on maize seeds grown on soil infested with Fusarium oxysporum and fertilized with N 180 P 140 K 90 and then in Morocco with the inoculation of Serratia proteamaculans (2025-1) on tomato [49]. Duponnois et al [50] indicated that the more robust the inoculated seedlings are than the un-inoculated plants, the more likely they are to survive by demonstrating a high capacity to withstand environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The R40 isolate was grown in a Luria Bertani (LB) medium under 100 rpm agitation and incubated at 28 • C for 78 h. Subsequently, 3 mL of the suspension was centrifuged at 4 • C for 10 min at 4,000 rpm (Moustaine et al, 2017). Then, 90 µL of the supernatant and 60 µL of the Salkowski reagent were placed in a microtube and incubated in the dark for 30 min to determine if a change in mean media color occurred (Gordon and Weber, 1951).…”
Section: Biochemical Tests Indole Acetic Acid Productionmentioning
confidence: 99%
“…On tomato plants, PGPR application could induct the plant's resistance from pests since decreasing the consumption level of Bemisia tabaci (Shavit et al 2013). At the harvesting, found that the average total yield of tomatoes treated with the PGPR significantly higher than that of the control and recorded a yield doubled compared to the control plants (Moustaine et al 2017).…”
Section: Introductionmentioning
confidence: 98%